Preliminary exploration of radiotherapy timing following induction chemoimmunotherapy in unresectable locally advanced esophageal squamous cell carcinoma: a single-center retrospective study - Zeng, Aiju; Zhang, Xianquan; Xu, Tian; Zhang, Yu; Ma, Daiyuan (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the efficacy and safety of the sequential strategy involving induction chemoimmunotherapy followed by radiotherapy for locally advanced unresectable esophageal squamous cell carcinoma (ESCC), and to explore the optimal timing for radiotherapy intervention and the potential clinical benefits of subsequent consolidative immunotherapy.MethodThis study retrospectively collected clinical data from treatment-naïve patients with unresectable T1-4N0-3M0 stage ESCC who underwent induction chemoimmunotherapy followed by radiotherapy at the Affiliated Hospital of North Sichuan Medical College between December 2021 and May 2024. Patients were stratified into two cohorts: the early radiotherapy cohort (early-RT, n=34), who initiated radiotherapy after completion of 1–2 cycles of induction chemoimmunotherapy, and the late radiotherapy cohort (late-RT, n=44), who initiated radiotherapy after completing 3–6 cycles of induction chemoimmunotherapy. The primary endpoints were progression-free survival (PFS) and overall survival (OS), with safety serving as the secondary endpoint.ResultWith a cutoff date of May 31, 2025, the median follow-up duration was 25.9 months. In the overall population, the median PFS was 16.0 months (95% confidence interval [CI], 11.7-20.3) and the median OS was 25.0 months (95%CI, 21.49-28.51). PFS was significantly longer in the early-RT cohort than in the late-RT cohort(20.4 vs. 13.7 months; HR = 0.53; p = 0.032). No statistically significant difference in OS was observed between the two cohorts (26.6 vs. 24.8 months; p = 0.728). Subsequent consolidative immunotherapy significantly improved PFS (median not reached [NR] vs. 12.8 months; HR = 0.46; p = 0.011) and OS (NR vs. 24.1 months; HR = 0.43; p = 0.017). In terms of safety, most treatment-related adverse events (TRAEs) were grade 1 or 2 in severity and were manageable. The incidence of toxicities did not differ significantly between the early-RT and late-RT cohorts (p > 0.05).ConclusionIn patients with unresectable locally advanced ESCC, the combination of early radiotherapy intervention and subsequent consolidative immunotherapy may represent a potential preferred therapeutic strategy. The findings from this study provide a rationale for the design of phase III clinical trials.